Prevalence of pigmentary disorders: A cross-sectional study in public hospitals in Durban, South Africa - Ncoza C. Dlova, MBChB, FCDerm, PhD; Lisa O. Akintilo, MD, MPH; Susan C. Taylor, MD (Wolters Kluwer, 2019)
Background: Pigmentary disorders are common in patients with skin of color and one of the top five most common dermatologic diagnoses in individuals of African descent. Little is known about the spectrum of pigmentary disorders in South Africa's second largest province, KwaZulu Natal. Objective: This study aimed to determine the profile of pigmentary disorders in patients at five outpatient public hospital skin clinics in Durban, South Africa. Methods: We collected data related to age, sex, ethnicity, and skin dyspigmentation diagnosis in a cross-sectional descriptive study of all dermatology patients at five public hospitals in Durban, South Africa between January 1 and March 31, 2015. The diagnosis was made on the basis of clinical grounds, supported by relevant laboratory investigations or histopathology where necessary. Only data relating to patients' first visit were recorded and captured using a Microsoft Excel 2007 spreadsheet. Results: A total of 304 patients, the majority of whom were African women (n = 230; 75.8%), were included in the study. The three most common pigmentary diagnoses included vitiligo, postinflammatory hyperpigmentation, and melasma. Conclusion: Dyschromias are the third most common dermatologic diagnosis in Durban, KwaZulu-Natal province, South Africa. The most common subtypes of pigmentary disorders include (in order of frequency) vitiligo, postinflammatory hyperpigmentation, and melasma. Keywords: African, black, dyschromia, dyspigmentation, ethnic skin, Indian, pigmentation, skin of color, South Africa